Association of fluid balance with 3-month outcomes in severe acute ischaemic stroke - Ming Liu; Simiao Wu; Xing Hua; Yanan Wang; Meng Liu; Linrui Huang (Stroke and Vascular Neurology)
Background Fluid therapy is commonly used for patients with severe stroke, for whom fluid balance is a safety endpoint for evaluating the therapy. We aimed to investigate the association of fluid balance with 3-month outcomes in patients with severe ischaemic stroke.Methods We enrolled patients with severe ischaemic stroke (National Institutes of Health Stroke Scale score ≥15) admitted to the department of neurology within 24 hours after the onset of stroke symptoms. Daily fluid balance volume in millilitres was defined as 24-hour fluid input minus fluid output. We calculated the mean value of daily fluid balance for the first 3 days after admission, and categorised patients as having positive fluid balance (daily fluid balance>+500 mL), even fluid balance (between −500 and +500 mL) and negative fluid balance (<−500 mL). The primary outcome was all-cause death at 3 months. We conducted multivariable logistic regression to investigate the association of fluid balance with 3-month death, with even fluid balance as the reference group.Results Of the 354 patients (mean age 73.1±12.9 years, 48.6% males) with severe ischaemic stroke, 94 patients (26.6%) had positive fluid balance, 194 patients (54.8%) had even fluid balance and 66 patients (18.6%) had negative fluid balance. Patients with positive fluid balance had a higher risk of 3-month death (adjusted OR 2.18, 95% CI 1.24 to 3.85, p=0.007), while patients with negative fluid balance did not show a significant difference (adjusted OR 1.68, 95% CI 0.88 to 3.20, p=0.115). The restricted cubic spline analysis illustrated a U-shaped trend of dose response relationship for mean daily fluid balance in relation to the adjusted OR of 3-month death (p for non-linearity=0.02).Conclusion In patients with severe ischaemic stroke, the positive fluid balance in the first 3 days was associated with a higher risk of death at 3 months.